Indigenous ecotourism: sustainable development and management - Zeppel, H. D.; Zeppel, H. D. (Wallingford :CABI, 2006)
This volume reviews indigenous ecotourism as a special type of nature-based tourism and examines the key principles of conservation and community benefits from indigenous-owned and operated ecotourism businesses and joint ventures. It compares indigenous tourism in developed and developing countries and provides global case studies of indigenous ecotourism projects in the Pacific Islands (village-based ecotourism in community rainforests), Africa (wildlife and forest ecotourism, the Maasai and community lands), Latin America (rainforest ecotourism, Andes mountains and Indian territories) and Southeast Asia (forest and mountain ecotourism, hill tribes and island nations). The book analyses key factors and constraints for sustainable development of indigenous ecotourism and explores the growing links with biodiversity conservation, ecotourism and indigenous rights. It will appeal to practitioners, researchers and students in ecotourism and sustainable tourism, indigenous studies, conservation, natural resource management and community development. The book has 9 chapters and a subject index.
Keywords: EE115 - Natural Resource Economics, (New March 2000); EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); PP700 - Biological Resources (General); UU450 - Community Participation and Development, (New March 2000); UU485 - Social Psychology and Social Anthropology, (New March 2000); UU700 - Tourism and Travel; Africa; Developed Countries; Developing Countries; Latin America; Pacific Islands; South East Asia